Transient angle stability analysis of maximum Lyapunov exponent based on the key branch response information - Niu, Zhenbo; Zheng, Chao; Lv, Sizhuo; Shan, Yunjing; Ni, Fengyi (Frontiers in Energy Research, 2024)
Based on real-time collection of perturbed response information from network nodes, this paper proposes an innovative on-line identification method for transient angle stability by combining the simplified branch transient transmission capability (sBTTC) index and the Maximum Lyapunov Exponent (MLE), aiming to enhance system stability assessment efficiency. Firstly, based on the two-machine system, this method investigates the consistency between the angle difference at both ends of the key branch and the group phase difference of the cluster. Secondly, by analyzing the sBTTC index variation pattern of the key branch, the transient angle stability issue is transformed into an MLE analysis problem. Furthermore, by analyzing the characteristics of the MLE curve and the sBTTC index curve, the transient angle stability criterion is given. Finally, the proposed method is substantiated and comprehensively assessed through simulation example. Due to its independence from a system model, ease of information source measurement, strong anti-noise ability, and elimination of the limitation of fixed symbol observation windows, this method exhibits strong industrial applicability.